High-service-life magnesium-aluminum-carbon sliding plate for special steel pouring and preparation process thereof
By using magnesium-aluminum carbon skateboards and using the synergistic effect of raw materials such as electromelted magnesium sand, the problem of short service life of existing skateboards in calcium-treated steel casting is solved, high-quality high-order continuous slip and heat resistance are achieved, and the service life and performance stability are significantly improved.
Patent Information
- Application Number
- CN202411654834.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
AI Technical Summary
Existing aluminum-zirconium carbon skateboards exhibit abnormal erosion and melt loss when pouring calcium-treated steel, and have a low service life, making it difficult to meet the requirements of calcium-treated steel and high oxygen steel.
Magnesium-aluminum carbon skateboard is used to improve the wear resistance and thermal shock resistance of the skateboard through the synergistic effect of electromelting magnesium sand, carbon materials, biological carbon, spinel, nano-alumina powder and other raw materials.
Magnesium aluminum carbon skateboard has good chemical stability and oxidation resistance in high temperature environments, which significantly improves service life, can achieve high-order continuous slips of more than 4 times, and reduces the consumption of refractory materials.
Smart Images

Figure BDA0005141877480000051 
Figure BDA0005141877480000061 
Figure BDA0005141877480000062
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, in particular to a high-life magnesium-aluminum-carbon slide plate for special steel casting and a preparation process thereof. Background Art
[0002] With the promotion of new steelmaking processes and the development of the steel market, calcium treatment technology has been promoted. In the smelting of special steels, in order to eliminate the blockage of the nozzle caused by aluminum deoxidation products, the molten steel needs to be treated with calcium. However, the corrosion of calcium-treated steel on refractory materials is aggravated, seriously affecting the service life and effect of the slide plate used for the sliding nozzle of the ladle.
[0003] At present, for the pouring of special steels such as high-oxygen steel and calcium-treated steel, aluminum-zirconium-carbon slide plates are commonly used for large ladle slide plates. Although aluminum-zirconium-carbon slide plates have good adaptability to steel types, they show abnormal corrosion and melting loss when pouring calcium-treated steel, and their service life is short, which brings hidden dangers to steelmaking. The slide plates for small and medium-sized ladles are mainly aluminum-carbon, and the processes are divided into three types: fired, lightly fired, and unfired. The service life is usually 1-3 times. Therefore, whether it is an aluminum-carbon slide plate or an aluminum-zirconium-carbon slide plate, its calcium erosion resistance is poor, and it is difficult to adapt to the use requirements of calcium-treated steel and high-oxygen steel. Summary of the invention
[0004] In order to solve the problems in the prior art, the present invention provides a high-life magnesium-aluminum-carbon slide plate for special steel casting and a preparation process thereof. The magnesium-aluminum-carbon slide plate obtained in the present application has a long service life, stable performance, and reduces the consumption of refractory materials.
[0005] The first aspect of the present invention is to provide a high-life magnesium-aluminum-carbon slide plate for special steel casting, which adopts the following technical solution: A high-life magnesium-aluminum-carbon slide plate for special steel casting comprises the following raw materials in parts by weight: 85-90 parts of fused magnesia, 1.5-3 parts of carbon material, 0.2-1 part of biochar, 3-6 parts of spinel, 0.5-1 part of nano alumina powder, 1-2 parts of metal silicon powder, 1-2 parts of metal aluminum powder, 0.5-2 parts of aluminum-magnesium alloy, 0.5-2 parts of aluminum-silicon alloy, 1-1.5 parts of metal zinc, 1 part of boron carbide, 1.8-2.2 parts of binder, 1.8-2.2 parts of silicone resin and 0.2 part of hexamine.
[0006] By adopting the above-mentioned technical scheme, the synergistic effect of the raw materials in the present application makes the magnesium-aluminum-carbon skateboard obtained in the present application have higher wear resistance and thermal shock resistance, and can reduce the wear and cracking of the skateboard during use, so that the magnesium-aluminum-carbon skateboard can be applied to calcium-treated steel ladles such as high-quality clean steel, special steel and alloy steel. More than 4 high-order continuous sliding (that is, after multiple consecutive sliding operations, the performance remains stable without obvious wear or damage). The main reasons are: the combination of fused magnesia with spinel and biochar effectively improves the chemical stability of the magnesium-aluminum-carbon skateboard at high temperature, thereby reducing the possibility of reaction with calcium in molten steel, thereby effectively improving the stability of the skateboard, and the combination of nano-alumina powder and nano-carbon black effectively improves the density and strength of the magnesium-aluminum-carbon skateboard, and can also significantly reduce the linear expansion rate of the magnesium-aluminum-carbon skateboard, thereby effectively improving the wear resistance and thermal shock resistance of the magnesium-aluminum-carbon skateboard in a high temperature environment; in addition, the combination of nano-carbon black and biochar can also effectively improve the hydration resistance of the magnesium-aluminum-carbon skateboard.
[0007] Preferably, the fused magnesia includes fused magnesia with a particle size of 3-1 mm, fused magnesia with a particle size of 1-0 mm, and fused magnesia with a particle size ≤0.075 mm in a weight ratio of (2.3-2.6):(3.6-3.9):1.
[0008] By adopting the above technical scheme, the fused magnesia is composed of fused magnesia with a particle size of 3-1mm, fused magnesia with a particle size of 1-0mm and fused magnesia with a particle size ≤0.075mm. It can effectively fill the pores inside the magnesium-aluminum-carbon skateboard and improve the density of the magnesium-aluminum-carbon skateboard, so that the magnesium-aluminum-carbon skateboard has good antioxidant properties and a longer service life.
[0009] Preferably, the carbon material is nano carbon black.
[0010] Preferably, the binder is lignosulfonate.
[0011] By adopting the above technical scheme, when wood sulfonate is selected as the binder, it can promote the formation of clustered silicon carbide whiskers inside the material at high temperature. The presence of clustered silicon carbide whiskers will be interwoven into a network structure, which plays an interlocking role and can better fill the pores inside the magnesium-aluminum-carbon skateboard, thereby reducing the contact area between the magnesium-aluminum-carbon skateboard and the air, and better inhibiting the air from entering the magnesium-aluminum-carbon skateboard to cause oxidation reaction, thereby improving the thermal shock resistance and oxidation resistance of the magnesium-aluminum-carbon skateboard.
[0012] Preferably, the particle size of the biochar is ≤0.075 mm.
[0013] Preferably, the particle size of the spinel is ≤0.075 mm.
[0014] Preferably, the particle size of the aluminum-magnesium alloy and the aluminum-silicon alloy is ≤0.045 mm.
[0015] Preferably, the particle size of the metallic zinc is ≤0.075 mm.
[0016] The second aspect of the present invention is to provide: a preparation process of a high-life magnesium-aluminum-carbon slide plate for special steel casting, comprising the following preparation steps: S1. Mixing mud materials: after mixing fused magnesia, biochar, spinel, metal silicon powder, metal aluminum powder and metal zinc, add a binder and mix for 3-4 minutes, add carbon material, nano-alumina powder, aluminum-magnesium alloy, aluminum-silicon alloy, boron carbide and hexamine and mix for 3-4 minutes, then add silicone resin and mix for 35-45 minutes to obtain a mixture; S2. The mixed material is molded, dried, sintered at 700-800°C under a reducing atmosphere, oil-impregnated, baked and cold-processed to obtain a magnesium-aluminum-carbon slide plate.
[0017] In summary, the present invention has the following beneficial effects: 1. The synergistic effect of the raw materials in the present application makes the magnesium-aluminum-carbon skateboard obtained in the present application have high wear resistance and thermal shock resistance, and can reduce the wear and cracking of the skateboard during use, so that the magnesium-aluminum-carbon skateboard can be applied to calcium-treated steel ladles such as high-quality clean steel, special steel and alloy steel. More than 4 high-order continuous sliding (that is, after multiple consecutive sliding operations, the performance remains stable without obvious wear or damage). The main reasons are: the combination of fused magnesia with spinel and biochar effectively improves the chemical stability of the magnesium-aluminum-carbon skateboard at high temperature, thereby reducing the possibility of reaction with calcium in molten steel, thereby effectively improving the stability of the skateboard, and the combination of nano-alumina powder and nano-carbon black effectively improves the density and strength of the magnesium-aluminum-carbon skateboard, and can also significantly reduce the linear expansion rate of the magnesium-aluminum-carbon skateboard, thereby effectively improving the wear resistance and thermal shock resistance of the magnesium-aluminum-carbon skateboard in a high temperature environment; in addition, the combination of nano-carbon black and biochar can also effectively improve the hydration resistance of the magnesium-aluminum-carbon skateboard.
[0018] 2. The addition of aluminum-magnesium alloy, aluminum-silicon alloy and metallic zinc can effectively improve the room temperature and high temperature strength and oxidation resistance of the magnesium-aluminum-carbon skateboard, thereby effectively increasing the service life of the magnesium-aluminum-carbon skateboard at high temperatures.
[0019] 3. In the present application, when the binder is selected as wood sulfonate, it can promote the formation of silicon carbide whiskers inside the material, so that the material has good oxidation resistance and thermal shock resistance. DETAILED DESCRIPTION
[0020] The present invention is further described in detail below with reference to the embodiments.
[0021] Example 1 A preparation process of a high-life magnesium-aluminum-carbon slide plate for special steel casting, comprising the following preparation steps: S1, mud mixing: 85kg of fused magnesia, 0.2kg of biochar, 3kg of spinel, 1kg of metal silicon powder, 1kg of metal aluminum powder, and 1kg of metal zinc were mixed, and 1.8kg of wood sulfonate was added and mixed for 3-4min, 1.5kg of nano carbon black, 0.5kg of nano alumina powder, 0.5kg of aluminum-magnesium alloy, 0.5kg of aluminum-silicon alloy, 1kg of boron carbide, and 0.2kg of hexamine were added and mixed for 3-4min, and 1.8kg of silicone resin was added and mixed for 35min to obtain a mixture; The purity of the fused magnesia is 98%, and the fused magnesia includes fused magnesia with a particle size of 3-1 mm, fused magnesia with a particle size of 1-0 mm, and fused magnesia with a particle size of ≤0.075 mm in a weight ratio of 2.3:3.6:1, that is, 28.3 kg of fused magnesia with a particle size of 3-1 mm, 44.3 kg of fused magnesia with a particle size of 1-0 mm, and 12.4 kg of fused magnesia with a particle size of ≤0.075 mm; The particle size of biochar is ≤0.075mm, the particle size of spinel is ≤0.075mm, the particle size of aluminum-magnesium alloy and aluminum-silicon alloy is ≤0.045mm, and the particle size of metal zinc is ≤0.075mm; S2. The mixed material is molded, dried, sintered at 700°C under a reducing atmosphere, oil-impregnated, baked and cold-processed to obtain a magnesium-aluminum-carbon slide plate.
[0022] Example 2 A preparation process of a high-life magnesium-aluminum-carbon slide plate for special steel casting, comprising the following preparation steps: S1, mud mixing: 87kg of fused magnesia, 0.5kg of biochar, 4.5kg of spinel, 1.5kg of metal silicon powder, 1.5kg of metal aluminum powder, and 1.2kg of metal zinc were mixed, and 2kg of wood sulfonate was added and mixed for 3-4min, 2kg of nano carbon black, 1kg of nano alumina powder, 1kg of aluminum-magnesium alloy, 1kg of aluminum-silicon alloy, 1kg of boron carbide, and 0.2kg of hexamine were added and mixed for 3-4min, and 2kg of organic silicone resin was added and mixed for 40min to obtain a mixture; The purity of the fused magnesia is 98%, and the fused magnesia includes fused magnesia with a particle size of 3-1 mm, fused magnesia with a particle size of 1-0 mm, and fused magnesia with a particle size of ≤0.075 mm in a weight ratio of 2.3:3.6:1, that is, 29 kg of fused magnesia with a particle size of 3-1 mm, 45.4 kg of fused magnesia with a particle size of 1-0 mm, and 12.6 kg of fused magnesia with a particle size of ≤0.075 mm; The particle size of biochar is ≤0.075mm, the particle size of spinel is ≤0.075mm, the particle size of aluminum-magnesium alloy and aluminum-silicon alloy is ≤0.045mm, and the particle size of metal zinc is ≤0.075mm; S2. The mixed material is molded, dried, sintered at 750°C under a reducing atmosphere, oil-impregnated, baked and cold-processed to obtain a magnesium-aluminum-carbon slide plate.
[0023] Example 3 A preparation process of a high-life magnesium-aluminum-carbon slide plate for special steel casting, comprising the following preparation steps: S1, mud mixing: 90kg of fused magnesia, 1kg of biochar, 6kg of spinel, 2kg of metal silicon powder, 2kg of metal aluminum powder, and 1.5kg of metal zinc were mixed, and 2.2kg of wood sulfonate was added and mixed for 3-4min, and 3kg of nano carbon black, 1kg of nano alumina powder, 2kg of aluminum-magnesium alloy, 2kg of aluminum-silicon alloy, 1kg of boron carbide, and 0.2kg of hexamine were added and mixed for 3-4min, and 2.2kg of organic silicone resin was added and mixed for 45min to obtain a mixture; The purity of the fused magnesia is 98%, and the fused magnesia includes fused magnesia with a particle size of 3-1 mm, fused magnesia with a particle size of 1-0 mm, and fused magnesia with a particle size of ≤0.075 mm in a weight ratio of 2.3:3.6:1, that is, 30 kg of fused magnesia with a particle size of 3-1 mm, 47 kg of fused magnesia with a particle size of 1-0 mm, and 13 kg of fused magnesia with a particle size of ≤0.075 mm; The particle size of biochar is ≤0.075mm, the particle size of corundum powder and spinel is ≤0.075mm, the particle size of aluminum-magnesium alloy and aluminum-silicon alloy is ≤0.045mm, and the particle size of metal zinc is ≤0.075mm; S2. The mixed material is molded, dried, sintered at 800°C under a reducing atmosphere, oil-impregnated, baked and cold-processed to obtain a magnesium-aluminum-carbon slide plate.
[0024] Example 4 A preparation process for a high-life magnesium-aluminum-carbon slide plate for special steel casting, which is different from Example 2 in that the total amount of fused magnesia is 87kg, of which the weight ratio of fused magnesia with a particle size of 3-1mm, fused magnesia with a particle size of 1-0mm and fused magnesia with a particle size of ≤0.075mm is 2.5:3.75:1, that is, 30kg of fused magnesia with a particle size of 3-1mm, 45kg of fused magnesia with a particle size of 1-0mm and 12kg of fused magnesia with a particle size of ≤0.075mm, and the rest are the same as Example 2.
[0025] Example 5 A preparation process for a high-life magnesium-aluminum-carbon slide plate for special steel casting, which is different from Example 2 in that the total amount of fused magnesia is 87kg, of which the weight ratio of fused magnesia with a particle size of 3-1mm, fused magnesia with a particle size of 1-0mm and fused magnesia with a particle size ≤0.075mm is 2.6:3.9:1, that is, 30.2kg of fused magnesia with a particle size of 3-1mm, 45.2kg of fused magnesia with a particle size of 1-0mm and 11.6kg of fused magnesia with a particle size ≤0.075mm, and the rest are the same as Example 2.
[0026] Example 6 A preparation process of a high-life magnesium-aluminum-carbon slide plate for special steel casting is different from that of Example 4 in that an equal amount of phenolic resin is used instead of wood sulfonate, and the rest is the same as Example 4.
[0027] Example 7 A preparation process of a high-life magnesium-aluminum-carbon slide plate for special steel casting is different from that of Example 4 in that an equal amount of nano-graphite is used instead of nano-carbon black, and the rest is the same as that of Example 4.
[0028] Comparative Example 1 A preparation process of a high-life magnesium-aluminum-carbon slide plate for special steel casting is different from that of Example 4 in that an equal weight of 98% sintered magnesia is used instead of 98% fused magnesia, and the rest is the same as Example 4.
[0029] Comparative Example 2 A preparation process of a high-life magnesium-aluminum-carbon slide plate for special steel casting is different from that of Example 4 in that an equal weight of corundum powder is used instead of spinel, and the rest is the same as Example 4.
[0030] Comparative Example 3 A preparation process of a high-life magnesium-aluminum-carbon slide plate for special steel casting is different from that of Example 4 in that the raw material lacks metallic zinc, and the rest is the same as Example 4.
[0031] Comparative Example 4 A preparation process of a high-life magnesium-aluminum-carbon slide plate for special steel casting is different from that of Example 4 in that biochar is lacking in the raw materials, and the rest is the same as Example 4.
[0032] Comparative Example 5 A preparation process of a high-life magnesium-aluminum-carbon slide plate for special steel casting is different from that of Example 4 in that the raw materials lack aluminum-magnesium alloy and aluminum-silicon alloy, and the rest are the same as Example 4.
[0033] Performance Testing The magnesium aluminum carbon slide plates obtained in the above embodiments and comparative examples were tested for volume density, porosity, compressive strength, room temperature flexural strength, high temperature flexural strength, linear expansion coefficient, and number of continuous sliding times. The test results are shown in Table 1.
[0034] Table 1 Magnesium aluminum carbon plate test results Table 1 From Table 1 above, we can see that: The magnesium-aluminum-carbon skateboards obtained in Examples 1-3 of the present application have a compressive strength greater than or equal to 105 MPa, a flexural strength greater than 25 MPa at room temperature, an adhesion strength greater than 17 MPa at 1400°C, and a linear expansion coefficient less than 1.3%, indicating that the magnesium-aluminum-carbon skateboards obtained in Examples 1-3 of the present application have good mechanical properties; in addition, the magnesium-aluminum-carbon skateboards obtained in Examples 1-3 of the present application have a thermal shock number greater than or equal to 10 times at 1100°C, a continuous sliding number greater than or equal to 5 times, and an oxidation area ratio less than 13% after oxidation at 1550°C for 3 hours. It can be seen that the magnesium-aluminum-carbon skateboards obtained in the present application have excellent thermal shock resistance and antioxidant properties, which effectively improves the service life of the magnesium-aluminum-carbon skateboard and reduces the cost of use.
[0035] Compared with Example 2, when the amount of fused magnesia added remains unchanged, after changing the weight ratio of fused magnesia with a particle size of 3-1 mm, fused magnesia with a particle size of 1-0 mm, and fused magnesia with a particle size of ≤0.075 mm, the porosity, linear expansion coefficient, and oxidation area ratio of the magnesium-aluminum-carbon slide plate obtained in Example 4-5 are reduced compared with those in Example 2, and the compressive strength, room temperature flexural strength, high temperature flexural strength, thermal shock number, and continuous sliding number are all increased compared with those in Example 2. It can be seen that the fused magnesia with a particle size of 3-1 mm and the fused magnesia with a particle size of 1-0 mm are The weight ratio of fused magnesia sand and fused magnesia sand with a particle size of ≤0.075mm has a certain influence on the mechanical properties, antioxidant properties and service life of the magnesium-aluminum-carbon skateboard. Moreover, with the increase of the weight ratio of 3-1mm fused magnesia sand and 1-0mm fused magnesia sand, the various performances of the magnesium-aluminum-carbon skateboard first increase and then decrease. It can be seen that when the weight ratio of 3-1mm fused magnesia sand, 1-0mm fused magnesia sand and 0.075mm fused magnesia sand is within the range specified in this application, the various performances of the magnesium-aluminum-carbon skateboard can be effectively improved.
[0036] Compared with Example 4, when an equal amount of phenolic resin is used instead of wood sulfonate, the thermal shock resistance, antioxidant performance and continuous sliding number of the magnesium-aluminum-carbon skateboard obtained in Example 6 are significantly reduced compared with those in Example 4. It can be seen that after the binder adopts wood sulfonate, it can promote the generation of clustered silicon carbide whiskers inside the material at high temperature. The presence of clustered silicon carbide whiskers will be interwoven into a network structure, which plays an interlocking role and can better fill the pores inside the magnesium-aluminum-carbon skateboard, thereby reducing the contact area between the magnesium-aluminum-carbon skateboard and the air, and better inhibiting the air from entering the magnesium-aluminum-carbon skateboard to cause oxidation reaction, thereby improving the thermal shock resistance and antioxidant performance of the magnesium-aluminum-carbon skateboard. When the binder adopts phenolic resin, the amount of silicon carbide whiskers generated inside the magnesium-aluminum-carbon skateboard is small, and it mainly exists in a granular morphology, so the antioxidant and thermal shock resistance are poor.
[0037] Compared with Example 4, when an equal amount of nano-graphite is used instead of nano-carbon black, the compressive strength, room-temperature flexural strength, high-temperature flexural strength, thermal shock resistance times, and continuous sliding times of the magnesium-aluminum-carbon slide plate obtained in Example 7 are significantly reduced compared with those in the examples. It can be seen that the strength formed by the combination of nano-carbon black and other components of the carbon material is better than that of graphite.
[0038] Compared with Example 4, when sintered magnesia of the same purity and weight is used instead of fused magnesia, the mechanical strength, linear expansion coefficient, number of continuous sliding times and oxidation resistance of the magnesium-aluminum-carbon slide plate obtained in Comparative Example 1 are all reduced compared with those in Example 4. The reason is that the volume of sintered magnesia changes greatly at high temperature, resulting in a loose structure and thus poor oxidation resistance. Although the thermal shock resistance of 98% sintered magnesia is improved compared with Example 4, the thermal shock resistance advantage is not significant. Therefore, the use of 98% fused magnesia can effectively improve the service life of the magnesium-aluminum-carbon slide plate.
[0039] Compared with Example 4, when the same weight of corundum powder is used instead of spinel, the high-temperature flexural strength, linear expansion coefficient, thermal shock resistance times and continuous sliding times of the magnesium-aluminum-carbon skateboard obtained in Comparative Example 2 are significantly reduced compared with those in Example 4. The reason is that after corundum powder is used instead of spinel, the magnesium-aluminum-carbon skateboard begins to expand in volume at 1200°C, resulting in an increase in the internal porosity of the magnesium-aluminum-carbon skateboard, and a significant reduction in the thermal shock resistance and oxidation resistance.
[0040] Compared with Example 4, when the raw materials lack metallic zinc or biocarbon or aluminum-magnesium alloy and aluminum-silicon alloy, the various performances of the magnesium-aluminum-carbon skateboard obtained in Comparative Examples 3-5 are lower than those in Example 4. It can be seen that the combination of metallic zinc with aluminum-magnesium alloy, aluminum-silicon alloy and biocarbon can not only improve the mechanical strength of the magnesium-aluminum-carbon skateboard, but also help to improve the antioxidant properties of the magnesium-aluminum-carbon skateboard, thereby extending the service life of the magnesium-aluminum-carbon skateboard.
[0041] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-life magnesium-aluminum-carbon slide plate for special steel casting, characterized in that: The invention comprises the following raw materials in parts by weight: 85-90 parts of fused magnesia, 1.5-3 parts of carbon material, 0.2-1 parts of biochar, 3-6 parts of spinel, 0.5-1 parts of nano alumina powder, 1-2 parts of metal silicon powder, 1-2 parts of metal aluminum powder, 0.5-2 parts of aluminum-magnesium alloy, 0.5-2 parts of aluminum-silicon alloy, 1-1.5 parts of metal zinc, 1 part of boron carbide, 1.8-2.2 parts of binder, 1.8-2.2 parts of silicone resin and 0.2 parts of hexamine.
2. The high-life magnesium-aluminum-carbon slide plate for special steel casting according to claim 1 is characterized in that: The fused magnesia sand includes fused magnesia sand with a particle size of 3-1 mm, fused magnesia sand with a particle size of 1-0 mm and fused magnesia sand with a particle size of ≤0.075 mm in a weight ratio of (2.3-2.6):(3.6-3.9):
1.
3. The high-life magnesium-aluminum-carbon slide plate for special steel casting according to claim 1 is characterized in that: The carbon material is nano carbon black.
4. The high-life magnesium-aluminum-carbon slide plate for special steel casting according to claim 1 is characterized in that: The binder is lignosulfonate.
5. The high-life magnesium-aluminum-carbon slide plate for special steel casting according to claim 1, characterized in that: The particle size of the biochar is ≤0.075 mm.
6. The high-life magnesium-aluminum-carbon slide plate for special steel casting according to claim 1, characterized in that: The particle size of the spinel is ≤0.075 mm.
7. The high-life magnesium-aluminum-carbon slide plate for special steel casting according to claim 1 is characterized in that: The particle size of the aluminum-magnesium alloy and the aluminum-silicon alloy is ≤0.045 mm.
8. The high-life magnesium-aluminum-carbon slide plate for special steel casting according to claim 1 is characterized in that: The particle size of the metallic zinc is ≤0.075 mm.
9. A process for preparing a high-life magnesium-aluminum-carbon slide plate for special steel casting as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following preparation steps: S1. Mixing mud materials: after mixing fused magnesia, biochar, spinel, metal silicon powder, metal aluminum powder and metal zinc, add a binder and mix for 3-4 minutes, add carbon material, nano-alumina powder, aluminum-magnesium alloy, aluminum-silicon alloy, boron carbide and hexamine and mix for 3-4 minutes, then add silicone resin and mix for 35-45 minutes to obtain a mixture; S2. The mixed material is molded, dried, sintered at 700-800°C under a reducing atmosphere, oil-impregnated, baked and cold-processed to obtain a magnesium-aluminum-carbon slide plate.
Citation Information
Patent Citations
Aluminum / zinc composite ultralow-carbon alumina-magnesite carbon brick for ladle lining
CN101774818A
Aluminum magnesium carbon sliding plate brick for stopping slag at steel tapping hole of converter
CN102249718A
Slide gate brick and preparation method thereof
CN105967702A
Slide plate brick for special steel and production method thereof
CN107042300A
Medium-temperature pretreatment low-carbon magnesian sliding plate brick containing modified graphite and preparation method thereof
CN108751948A